1991
DOI: 10.1007/bf00183587
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of FK973: Description of a delayed vascular leak syndrome

Abstract: FK973 is a novel, substituted dihydrobenzoxazine structurally similar to mitomycin. FK973 lacks cross-resistance with mitomycin, doxorubicin, and vincristine in murine tumor models. A phase I study of FK973 was initiated using a 30-minute infusion repeated every 4 weeks. Of 17 patients enrolled on the study, a minimum of three patients were entered at each dose level: 7, 14, 21, 30, and 45 mg/m2. The dose-limiting toxicity was a vascular leak syndrome (VLS) characterized by pericardial and pleural effusions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…5,6) Various FK973 derivatives were synthesized in an attempt to isolate the antitumor activity of FK973 from the VLS side effect, and FK317, 11-acetyl-8-carbamoyloxymethyl-4-formyl-6-methoxy-14-oxa-1, 11-diazatetracyclo-[7.4.1.0 2, 7 .0 10, 12 ]tetradeca-2,4,6-trien-9-yl acetate, was selected for further examination. FK317 showed similar antitumor activity to FK973, but did not induce pleural effusion in rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6) Various FK973 derivatives were synthesized in an attempt to isolate the antitumor activity of FK973 from the VLS side effect, and FK317, 11-acetyl-8-carbamoyloxymethyl-4-formyl-6-methoxy-14-oxa-1, 11-diazatetracyclo-[7.4.1.0 2, 7 .0 10, 12 ]tetradeca-2,4,6-trien-9-yl acetate, was selected for further examination. FK317 showed similar antitumor activity to FK973, but did not induce pleural effusion in rats.…”
Section: Introductionmentioning
confidence: 99%
“…4) FK973 showed good efficacy in clinical studies, but its development was terminated because of a vascular leak syndrome (VLS) side effect which was characterized by pericardial and pleural effusion, ascites and subcutaneous edema. 5,6) Various FK973 derivatives were synthesized in an attempt to isolate the antitumor activity of FK973 from the VLS side effect, and FK317, 11-acetyl-8-carbamoyloxymethyl-4-formyl-6-methoxy-14-oxa-1, 11-diazatetracyclo-[7.4.1.0 2,7 .0 10,12 ]tetradeca-2,4,6-trien-9-yl acetate, was selected for further examination. FK317 showed similar antitumor activity to FK973, but did not induce pleural effusion in rats.…”
mentioning
confidence: 99%
“…5,6) We sought a new compound having the same potent anti-tumor activity as FK973, but without the undesirable side effect, and selected FK317 (11-acetyl-8-carbamoyloxymethyl-4-formyl-6-methoxy-14-oxa-1,11-diazatetracyclo[7.4.1.0 2, 7 .0 10, 2 ]-tetradeca-2,4,6-trien-9-yl acetate) as a candidate from among various derivatives of FK973. FK317 is a deacetylated derivative of FK973.…”
mentioning
confidence: 99%
“…[2][3][4] However, during phase I clinical trials of FK973, vascular leak syndrome was observed in patients following FK973 treatment and it was thus withdrawn from development; nevertheless it showed therapeutic anti-tumor activity in some of the cancer patients enrolled in the clinical trial. 5,6) We sought a new compound having the same potent anti-tumor activity as FK973, but without the undesirable side effect, and selected FK317 (11-acetyl-8-carbamoyloxymethyl-4-formyl-6-methoxy-14-oxa-1,11-diazatetracyclo[7.4.1.0 2,7 .0 10,2 ]-tetradeca-2,4,6-trien-9-yl acetate) as a candidate from among various derivatives of FK973. FK317 is a deacetylated derivative of FK973.…”
mentioning
confidence: 99%
“…However we were unable to develop this compound because it induces vascular leak syndrome (VLS) as a major side effect. 2,3) In attempts to synthesize new FK973 derivatives which retain the antitumor activity, without the VLS side effect, FK317, 11-acetyl-8-carbamoyloxymethyl-4-formyl-6-methoxy-14-oxa-1,11-diazatetracyclo[7.4.1.0 2,7 .0 10,12 ]tetradeca-2,4,6,-trien-9-yl acetate, was identified. This agent has a unique bicyclic hydroxylamine hemiketal ring system, and its antitumor activity is more potent than, or equivalent to, that of mitomycin C (MMC), adriamycin (ADR), cisplatin (CDDP), taxol or irinotecan hydrochloride against murine tumors and human xenografts in mice.…”
mentioning
confidence: 99%